GROUP COMMUNICATION PROCESS BETWEEN MOBILE LEGEND GAME PLAYERS IN PENDEKAR ESPORTS COMMUNITY - Alicia Marissa Wirajaya Hosky; Tangguh Okta Wibowo (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
This research highlights how mobile gaming, and in particular Mobile Legend, has evolved from mere entertainment to a professional field that generates revenue. Players, especially in e-sports teams such as Pendekar Esports, have created complex communities with symbolic interactions that influence each other and lead to cooperation to achieve victory in competition. This research uses the case study method on an Esports team, Pendekar Esports, to further research related to the communication of the interactions that are built. The results of this study increase the complexity of the communication and interaction process that takes place in the world of e-sports, proving that games are not just entertainment, but also bring out significant social and professional dynamics. This research applies symbolic interactionism theory to describe individual views of the team, changes in identity when becoming a professional player, and the impact of the team environment on players' attitudes and behaviour. The concept of 'spirit' illustrates the motivation of players to combine hobbies and income in Pendekar Esports. The concept of "self" illustrates the transformation of the player's identity into a professional with the impact of discipline and professional attitude. The concept of "society" reveals the role of the team environment in shaping communication and discipline. The study shows that in e-sports, adaptation to specific changes in identity, norms and language affects the dynamics of communication and player behaviour. The interaction of individuals in groups in an e-sports team leads to significant changes in players' views, attitudes and interactions.